Effect of fertigation with domestic sewage effluent in the performance of self-compensating sprinklers - Pitoro, Valdemiro [UNESP]; Román, Rodrigo Sánchez [UNESP]; Queluz, João [UNESP]; Ventura, Kevim [UNESP] (Centro Universitario de Maringa, 2022)
Irrigation by sprinklers is a trustworthy and efficient method for the application of domestic sewage effluent (EED) in agricultural fertigation. Its weakness lies in the possibility of sprinkler obstruction. Current paper evaluates the behavior of self-compensating sprinklers by applying EED treated in anaerobic filters. Assay was conducted in two culture systems: conventional culture (SCC) and vertical (SCV) systems, and irrigation with water of different qualities (treatments): T1 - irrigation with 100% treated effluent (EFT); T2 - irrigation with 100% tap water (AAB); T3 - irrigation with 50% EFT and 50% AAB. Evaluation of the effect of irrigation water quality in the performance of sprinklers in SCC was based on the coefficient of uniformity of distribution (CUD), the coefficient of statistic uniformity (CUE) and the coefficient of manufacturing variation (CVf); in the case of SCV, it was based on the coefficient of variation (Cv) of discharge. Result showed that sprinklers in both culture systems revealed excellent performance. CUD and CUE rates were higher than 90% and may be classified as excellent; CVf of treatments T1 and T3 were classified as fair and T2 as excellent. Cv of discharge in all treatments was below 7% and showed that water quality of irrigation water failed to change the standard of sprinklers in SCV. Irrigation with sewage effluent treated in anaerobic filters did not affect the performance of sprinklers in the two culture systems and revealed excellent performance by EED treatment applied.
Efeito da fertirrigação com efluente de esgoto doméstico no desempenho de gotejadores autocompensantes
Keywords: Irrigation by sprinklers; Obstruction of sprinklers; Performance of sprinklers; Reuse of effluents